Interaction of excitons with Cherenkov radiation in WSe2 beyond the non-recoil approximation. (4th January 2022) - Chahshouri, Fatemeh; Taleb, Masoud; Diekmann, Florian K; Rossnagel, Kai; Talebi, Nahid
Abstract: Cherenkov radiation (CR) from electrons propagating in materials with a high refractive index have applications in particle-detection mechanisms and could be used for high-yield coherent electron beam-driven photon sources. However, the theory of the CR has been treated up to now using the non-recoil approximation, which neglects the effect of electron deceleration in materials. Here, we report on the effect of electron-beam deceleration on the radiated spectrum and exciton-photon interactions in nm-thick WSe2 crystals. The calculation of the CR is performed by simulating the kinetic energy of an electron propagating in a thick sample using the Monto Carlo method combined with the Lienard–Wiechert retarded potential. Using this approach, we numerically investigate the interaction between the excitons and generated photons (CR) beyond the non-recoil approximation and are able to reproduce experimental cathodoluminescence spectra. Our findings pave the way for an accurate design of particle scintillators and detectors, based on the strong-coupling phenomenon.